Effect of supplemental vibration on tooth movement and treatment time with clear aligners. A systematic review and meta-analysis - Gandhi, Rasiga; Ravi, Janani; Siva, Suvetha; Kishore, Shreya; Mathew, Suman Manoj (Brazilian Dental Science, 2025)
Aim: The aim of this systematic review and meta-analysis was to evaluate the effect of supplemental vibrational force on tooth movement and treatment duration in patients undergoing treatment with clear aligners. Material and Methods: Electronic searches were carried out without any restriction in PubMed, the Cochrane Library, the Directory of Open Access Journals, LILACS, and Google Scholar. The revised Cochrane risk of bias tool (RoB 2.0) for randomized controlled trials, the Risk of Bias in Nonrandomized Studies of Intervention (ROBINS-I) tool for prospective studies, and the Newcastle-Ottawa Scale for retrospective studies were used. Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was used to assess the quality of evidence. Random effects meta-analysis with standardized mean difference (SMD) was carried out using Review Manager software (Revman 5.4). Results: Ten studies met the inclusion criteria for this systematic review. While some studies reported a reduction in aligner change intervals and improved tracking, the overall clinical impact on treatment duration was limited. Meta-analysis demonstrated a statistically significant decrease in aligner exchange rate with the use of supplemental vibration (SMD = -2.36; 95% CI: -4.52 to -0.21; p = 0.03), although no consistent improvement in final tooth alignment or total treatment time was observed. Conclusion: There is limited evidence on the effect of supplemental vibration of aligners. The meta-analysis indicates that while supplemental vibration may significantly reduce the aligner exchange rate, it does not result in a statistically significant improvement in incisor alignment or reduction in the total number of aligners required for treatment completion. These findings suggest limited clinical benefit of vibrational force in enhancing overall treatment efficiency with clear aligners. KEYWORDS Acceleration; Clear aligner; Orthodontic appliances; Tooth movement; Vibration.